MOTRIC ABILITY DEVELOPMENT OF Vth GRADE STUDENTS THROUGH HANDBALL GAME METHODS - Petrariu Ileana (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
This study aims to highlight the importance of handball game methods to develop motric ability for Vth grade students. This study was conducted on a group of 23 students. They were initially applied a series of tests to determine the motor ability development level. After initial testing, the children attended a training program with the specific handball methods. The final tests were applied in order to determine the students training level. Following statistical and mathematical interpretation of the results was determined the students progress.